La construcción de la historia subjetiva en la clínica psicológica (2010)
ABSTRACT: This paper tackles the issue of history in the clinical practice of psychology. The starting point is composed of three hypotheses: (1) suffering places itself in the subjective history that the patient has built; (2) the clinical practice of psychology aims at construction of subjective patients, and (3) the history at which the patient arrives is not discovered, but built, rebuilt and in constant change. This approach makes use, on the one hand, of thoughts of contemporary philosophers regarding the issue of history in postmodernity; and on the other hand, of a clinical case that serves as an example for such discussion. It is concluded that the past is not history; that history is a fabric that comprises past experiences, as well as the present and the future; that this fabric changes constantly and can be (re)built, so that subjective suffering can or cannot be reduced. And, lastly, that the clinical practice of psychology contributes to the building of the patient’s subjective history. Key Words: subjective history, clinical practice, postmodernity.